Pengaruh Motivasi, Disiplin Dan Kecerdasan Spiritual Terhadap Produktivitas Kerja Pegawai Pasca Pandemi Covid–19 - Aa Willy Nugraha; Bekti Wulandari; Reki Apriadi (EKOBIMA, 2023)
The purpose of this reseach were to determine: (a) Motivation, Discipline of Spiritual Intelligence and Employees productivity, (b) How the influence of Motivation, Discipline and Spiritual Intelligence on Employees productivity together. (c) How is the effect of motivation, discipline and spiritual intelligence on employees productivity partially at PT PLN (Persero) Tasikmalaya City and Tasikmalaya Regency. The research method used is the census method. The study found that: (a) The motivation variable is in the good category, and discipline, spiritual intelligence and employee employees productivity are in the very good category. (b) Together, there is a significant influence between motivation, discipline, spiritual intelligence on employee employees productivity. (c) Partially there is a significant positive effect between motivation, discipline, spiritual intelligence on employees productivity.